2000
DOI: 10.1093/emboj/19.15.4064
|View full text |Cite
|
Sign up to set email alerts
|

A repressor sequence in the juxtamembrane domain of Flt-1 (VEGFR-1) constitutively inhibits vascular endothelial growth factor-dependent phosphatidylinositol 3′-kinase activation and endothelial cell migration

Abstract: Vascular endothelial growth factor (VEGF) has two highly homologous tyrosine kinase receptors: Flt‐1 (VEGFR‐1) and KDR (VEGFR‐2). KDR is strongly phosphorylated on tyrosines and can transmit mitogenic and motogenic signals following VEGF binding, while Flt‐1 is markedly less effective in mediating such functions. To dissect the regions that account for the differences between the two receptors, we generated a series of chimeric Flt‐1–KDR molecules. We found that the juxtamembrane region of Flt‐1 prevents key s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 51 publications
(57 reference statements)
5
107
1
Order By: Relevance
“…VEGFR-1 has no aberrant amino-acid replacement in these regions, suggesting that its kinasedefective phenotype is not associated with structural abnormality within the kinase domain. Replacement of the JM (Juxtamembrane) region of VEGFR-1 with that of VEGFR-2 also does not rescue its poor liganddependent kinase activation (Gille et al, 2000). Our current study shows that the kinase-defective phenotype of VEGFR-1 is linked to its carboxyl tail.…”
Section: Discussioncontrasting
confidence: 48%
“…VEGFR-1 has no aberrant amino-acid replacement in these regions, suggesting that its kinasedefective phenotype is not associated with structural abnormality within the kinase domain. Replacement of the JM (Juxtamembrane) region of VEGFR-1 with that of VEGFR-2 also does not rescue its poor liganddependent kinase activation (Gille et al, 2000). Our current study shows that the kinase-defective phenotype of VEGFR-1 is linked to its carboxyl tail.…”
Section: Discussioncontrasting
confidence: 48%
“…Our study demonstrates that Etk mediates the TNF-induced PI3K-Akt angiogenic pathway, which has been well documented in growth factor-stimulated cell migration (41)(42)(43)(44). PI3K-Akt may induce angiogenesis by multiple downstream effectors including the Rho family of small GTPases, PAK1, and endothelial nitric-oxide synthase (14,(41)(42)(43)(44). Further investigation is required to determine which of these Etk effector(s) contributes to TNF-induced angiogenesis.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, Etk through its PH domain binds to and activates PAK1 (36), a 65-kDa serine/ threonine kinase implicated in integrin-induced EC migration and angiogenesis by modulating EC contraction (37). Our study demonstrates that Etk mediates the TNF-induced PI3K-Akt angiogenic pathway, which has been well documented in growth factor-stimulated cell migration (41)(42)(43)(44). PI3K-Akt may induce angiogenesis by multiple downstream effectors including the Rho family of small GTPases, PAK1, and endothelial nitric-oxide synthase (14,(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 56%
“…Two studies using chimeras of VEGFR-1 and VEGFR-2 have found that these chimeras suppress VEGFR-2-mediated proliferation, but not migration (63,64). Exchanging the juxtamembrane region of the VEGFR-2 with VEGFR-1 suppresses VEGFR-2-mediated signaling and migration (65).…”
Section: Vegf-induced Signal Transduction and Endothelial Functionmentioning
confidence: 99%